Osteosarcoma in a Child Below 2 Years of Age: Case Report and Review of the Literature. Issue 5 (July 2019) - Pascoe, Edward M.; Free, Matthew; Mackie, Peter S.; Donnan, Leo; O'Sullivan, Mark; Sullivan, Michael J.; Heath, John A.
Abstract : Background: Osteosarcoma in children below the age of 5 is extremely rare. Observation: We report on a previously well 14-month-old male infant, who presented with a reluctance to weight-bear on his right leg and had an associated limp. Plain imaging and a magnetic resonance imaging scan demonstrated a lytic lesion in the right distal femur. An open surgical biopsy confirmed the diagnosis of osteosarcoma. There was no significant family history of cancer and genetic screening for Li-Fraumeni syndrome was negative. Conclusions: This case highlights the importance of timely consideration of osteosarcoma in an infant, when the clinical presentation and medical imaging are consistent with that diagnosis.